Excesso no infravermelho e discos de detritos em torno de estrelas subgigantes Kepler - Silva, Danielly Freire da (2019)
Studies about circumstellar material in different evolutionary stages has been increasingly developing due to the emergence of high photometric resolution space missions, covering an even larger spectrum of infrared wavelength. Among them missions, Spitzer, Herschel and W ISE, for instance, present a particular aspect by offering observations in wavelength compatible to the temperature of the Solar System’s Asteroid Belt and Zodiacal Cloud. In this present thesis, a search for debris disk is performed around 34030 objects, defined in the literature as being in the Main Sequence, observed by the Kepler mission and based on the W ISE mission photometric information. At first, a diagnosis is performed on the presence of infrared excess on these stars. This detection is potentially associated to the presence of circumstellar material. Then, a study is made about the evolutionary stage of the sample, including their location on the HR diagram. This analysis was done based on data from the GAIA mission and showed that only about 16500 stars are actually Main Sequence, with around 17000 presenting characteristics of Subgiants or binary systems, according to their location. By utilizing data treatment tools, including VOSA, this work has shown the presence of debris disk around 35 Main Sequence stars, 13 Subgiants and one anomalous star, with well defined locations in the HR diagram, raising questions about the physical characteristics of these disks in relation to the stellar age. The Main Sequence stars possess debris disks that are more massive and more luminous than the Solar System’s Asteroid Belt and Zodiacal Cloud, bringing up the possibility that the disk was refueled with additional material, produced by violent stochastic events, including the disintegration of large bodies such as planets or massive asteroids. In Subgiants stars, on average, the mass and luminosity of the disks are in the same order as the values seen in the Main Sequence stars, this is incompatible with the notion that these disks are first generation remnants and have survived the first evolutionary stages. Therefore, such results seem to point to the presence of dynamical physical processes happening in the circumstellar environment during the Subgiant stage, refueling the disks with material produced in this stellar evolutionary stage. Therefore, the disk around the Subgiants found in this work can not be explained solely by the evolutionary context or under the consideration that they were preserved during the passage from the Main Sequence to the Subgiant stage and along the evolution outside the Main Sequence.